PREPARAÇÃO DE COMPÓSITOS DE POLIANILINA EM MATRIZES DE COPOLÍMEROS ESTIRENO-DIVINILBENZENO E ESTUDOS DE ADSORÇÃO POR TROCA IÔNICA DE ÂNIONS COMPLEXOS DE [FeCl4]- E [CuCl4]2- - SILVA, Robson Benedito (2008)
In this work, composites of dispersed polyaniline in beads of styrenedivinybenzene copolymer (Pani/Sty-DVB copopolymer) with different porosities were prepared through in situ polymerization. Materials with high surface areas and high porosities were obtained what explain their properties to adsorve transition metals. SD29 and SD84 copolymers were prepared through suspension polymerization in the presence of inert diluents as toluene/heptane with different DVB ratios to obtain macroporous beads. SD29/Pani and SD84/Pani composites were obtained by swelling the copolymers with aniline/ethanol mixtures (20/80%) before polymerization. Oxidative polymerization of aniline was carried out with ammonium persulfate in the presence of nitric acid at pH extremely acid and temperature range from 0 to 3 oC for 5 hours. All materials were characterized by infrared spectroscopy, porosity measurements, optical microscopy and adsorption capacity. The composite surface areas and pore volumes diminished in relation to original xv copolymers, while apparent density increased due polyaniline incorporation. Pore size distributions did not suffer large variations and all were typical of macroporous structures. Due the high DVB content, SD84/Pani composite and SD84 copolymer presented higher porosity and specific surface area when compared to systems with low reticulation degree. From acid solutions, [FeCl4]- and [CuCl4]2-, complex anions were adsorbed on SD29/Pani and SD84/Pani composites through ion exchange batch process. The amounts of complex anions adsorbed were determined by atomic absorption spectrophotometry. Complex anions adsorption increased with chloridric acid and metal concentration for both composites. Maximum adsorption capacity (mg of anion/g of composite) of [FeCl4]- were higher than [CuCl4]2- for both composites. Kinetic data showed a time of 12h for adsorption equilibrium of [FeCl4]- anions, while for [CuCl4]2- anions the equilibrium was not reached in 24 h for both composites. Infrared spectra showed vibrational bands of characteristic functional groups in the materials and band shifts were observed after [FeCl4]- and [CuCl4]2- complex anions adsorptions on the composites. Morphology evaluation showed that aniline polymerized homogeneously in the presence of nitric acid for all porous structures of the copolymers. Therefore, it can be concluded that complex anions adsorption depend as so the amount of adsorption sites of polyaniline as the porous structures of the composites.